Peningkatan Kesadaran Gizi melalui Program Sosialisasi Konsumsi Susu pada Anak Usia Dini di Desa Bonto Karaeng, Kecamatan Sinoa, Kabupaten Bantaeng - Juanda, Juanda; Ramadani, Dewi; Lestari, Rika Hari (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
At present there is a lack of awareness among parents about the importance of nutrition in the growth of early childhood, one of which is that knowledge about milk consumption is not evenly distributed in society. This socialization aims to increase parental awareness about nutrition by teaching young children to consume milk. The 2024 ISS-MBKM PKKM THEMATIC Real Work Program (KKN) activities at Muhammadiyah Bone University, carried out in August 2024 in Bonto Karaeng Village, Sinoa District, Bantaeng Regency, this activity aims to improve nutrition through milk consumption in early childhood. The methods used include observation, counseling and distribution of free milk which was carried out at community health centers and posyandu which were attended by mothers and children, followed by socialization. The results obtained were an increase in community knowledge in Bonto Karaeng Village about the importance of milk consumption in early childhood to meet nutritional status. With socialization carried out in the community, it can provide awareness to parents to always fulfill nutrition in early childhood for the sake of children's growth. In this activity, initially we wanted to use pure milk, but it was difficult to find pure milk nearby, so we used packaged milk (Clevo milk) as a sample from this program. This activity can make parents aware of the importance of consuming milk every day to maintain body health.